Supramolecular interaction facilitated block copolymer assembly and preparation of self-organized scaffold for chiral selective transport. (7th November 2018) - Sun, Zhijuan; Li, Xuan; Zhu, Guodong; Xue, Lixin; Zhou, Yong; Yi, Zhuan; Gao, Congjie
Abstract: Self-assembly of block copolymers (BCPs) is strongly dependent on molecular compositions. However, there are many BCPs having compositions less than the lower limit that is required to induce the self-assembly, and self-organized membranes can be hardly prepared from them. To solve this problem, we described a method to fabricate self-organized membranes consisted of worm-like aggregates through the supramolecular interaction facilitated assembly. The polystyrene- block -poly(4-vinylpyridine) (PS4VP) with a P4VP fraction of 8.8 wt% was used as the material, and membranes were prepared through the SNIPS process. Sulfonated polyethylene glycol (SPEG) interacting with P4VP was developed as the supramolecular additive for the PS4VP, and effects of the ratio of SPEG to 4VP on membrane formation were systematically studied. It was found that SPEG not only facilitated the assembly of PS4VP into worm-like aggregates, but also increased the porosity and permeability of the membranes. The self-organized membranes were then transformed into chiral filters through metal deposition and cysteine immobilization. It was determined that the transport rates and transport coefficient (αL/D ) of resultant chiral membranes for bovine serum albumin molecules reached 6.53 nmol/cm 2 .h and 1.73, respectively, both of which were obviously higher than that of plain membranes prepared from the same BCP with inferior assembly. Our results demonstrated that the additive facilitated assembly was crucial to the performace improvement of those BCPs that were unable to self-assemble into organized membranes. Graphical abstract: Highlights: Supramolecular interaction facilitated BCP assembly was described. Symmetric membranes consisted of elongated aggregates were prepared. These self-organized membranes were used as scaffolds for chiral selective transport. Chiral filters derived from organized membranes delivered superior permselectivity.